THE EFFECTS OF SELECTED PILATES EXERCISE ON THE BODY COMPOSITION OF OBESE PEOPLE - Tyagi, Rahul; Kumar, Pravin (International Journal of Psychosocial Rehabilitation, 2019)
The purpose of the present study was to find out the effect of selected Pilates exercises on body composition of obese people. The total sample of 60 males between the age group of 20-45 years was selected and divided into two groups i.e. 30 in the experimental group and 30 in the control group from the general population of Muzaffarnagar Uttar Pradesh. In the present study, a purposive-random sampling technique was employed to select the sample for measuring Body weight, body mass index, body fat percentage & visceral fat level. The subjects underwent training for 24-week with the Pilates exercises. The difference in the mean of each group for selected variables was tested for the significance of difference by paired ‘t’ test. The level of significance was set at 0.05. The Result was found that the effect of selected Pilates exercises was significant Body weight, body mass index, body fat percentage& visceral fat level of the experimental group as compared to the control group.